A normative decision-making model for cyber security. (17th June 2019) - M'manga, Andrew; Faily, Shamal; McAlaney, John; Williams, Chris; Kadobayashi, Youki; Miyamoto, Daisuke
Abstract : Purpose: The purpose of this paper is to investigate security decision-making during risk and uncertain conditions and to propose a normative model capable of tracing the decision rationale. Design/methodology/approach: The proposed risk rationalisation model is grounded in literature and studies on security analysts' activities. The model design was inspired by established awareness models including the situation awareness and observe–orient–decide–act (OODA). Model validation was conducted using cognitive walkthroughs with security analysts. Findings: The results indicate that the model may adequately be used to elicit the rationale or provide traceability for security decision-making. The results also illustrate how the model may be applied to facilitate design for security decision makers. Research limitations/implications: The proof of concept is based on a hypothetical risk scenario. Further studies could investigate the model's application in actual scenarios. Originality/value: The paper proposes a novel approach to tracing the rationale behind security decision-making during risk and uncertain conditions. The research also illustrates techniques for adapting decision-making models to inform system design.